2014
DOI: 10.5487/tr.2014.30.2.091
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Habits and Neuropeptides: Adiponectin, Brain-derived Neurotrophic Factor, and Leptin Levels

Abstract: This study aimed to identify changes in the level of neuropeptides among current smokers, former smokers, and individuals who had never smoked, and how smoking habits affect obesity and metabolic syndrome (MetS). Neuropeptide levels, anthropometric parameters, and metabolic syndrome diagnostic indices were determined among male workers; 117 of these had never smoked, whereas 58 and 198 were former and current smokers, respectively. The total sample comprised 373 male workers. The results obtained from anthropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Independent reverse association between smoking and adiponectin was reported. 55 , 56 In our group we found that examinees that never smoked had borderline significantly higher adiponectin values than ex-smokers and current smokers, and observed a negative association with log adiponectin where every pack-year decreased adiponectin concentration for 1 mg/L. However, we were not able to confirm that smoking is an independent predictor of adiponectin concentration in normotensives and untreated, newly diagnosed hypertensives.…”
Section: Discussionmentioning
confidence: 57%
“…Independent reverse association between smoking and adiponectin was reported. 55 , 56 In our group we found that examinees that never smoked had borderline significantly higher adiponectin values than ex-smokers and current smokers, and observed a negative association with log adiponectin where every pack-year decreased adiponectin concentration for 1 mg/L. However, we were not able to confirm that smoking is an independent predictor of adiponectin concentration in normotensives and untreated, newly diagnosed hypertensives.…”
Section: Discussionmentioning
confidence: 57%
“…However, we could not compare above data, because the experiments were performed different time, age and genders were not matched, and also factors influence BDNF, MHPG, HVA were heterogeneous in the both group. For example, body mass index ( 27 ), smoking ( 28 ), and personality traits also influence serum BDNF levels ( 29 ). In short, the two groups have different back ground, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the level of ADPN progressively decreased with the extension of HS time and progressively increased after the recovery treatment of HS mice. Therefore, we hypothesize that a reduction in ADPN is involved in full-body pathophysiological changes after induction of HS (Kim et al, 2014;Lian et al, 2015;Safai et al, 2015). We found that ADPN could be used as an anti-inflammatory cytokine, which can instantly and effectively reverse HS and its concomitant pathophysiological changes in the body during post-shock recovery.…”
Section: Discussionmentioning
confidence: 89%